Foodways of Enslaved Laborers on French West Indian Plantations (18th-19th century) - Kenneth G. Kelly; Diane Wallman (Afriques)
In the plantation settlements of the Americas, enslaved Africans and their descendants were compelled to create a system of foodways that provided sufficient nutrition for their survival and that could be assembled out of the resources available to them. The ability of the enslaved plantation workers to do this is a testament to their creativity, and the cuisine they developed lives on today in the creole foods of the former slave colonies. The foods, the methods of their procurement, the methods of preparation, and the artifacts used in that preparation consist of a blend of African, European, and American influences reflecting environment, cultural heritage, and economics. In this article, we integrate ethnohistorical and historical documents with archaeological materials from excavations at two plantation slave villages, one in Guadeloupe and one in Martinique, in the context of Caribbean creole foodways within the French West Indies.